Prevalence, antimicrobial susceptibility profile, and associated risk factors of uropathogenic Escherichia coli among pregnant women attending Dr. Sumait Hospital Mogadishu, Somalia - Mohamed, Fartun Yasin; Dahie, Hassan Abdullahi; Mohamoud, Jamal Hassan; Adam, Mohamed Hussein; Dirie, Hassan Mohamud (Frontiers in Public Health, 2024)
Uropathogenic Escherichia coli (UPEC) is the strain of E. coli commonly associated with urinary tract infections. Besides, Antibiotic resistance in UPEC is one of the most significant health problems. This study was conducted to determine the prevalence, antimicrobial resistance, and factors linked to Uropathogenic Escherichia coli (UPEC) in pregnant women.This cross-sectional study was conducted within a hospital setting, between August 2022 and December 2022. Using consecutive convenient sampling, the research enrolled 220 pregnant women. The urine samples obtained from these women was cultured on MacConkey and blood agar and incubated at 37°C overnight, followed by sub-culturing on Mueller Hinton media.Bacterial identification involved Gram staining and biochemical characterization (TSI, indole, citrate, methyl red, urea agar, and motility tests). Conversely, susceptibility tests were performed using the Kirby-Bauer disc diffusion method. A binary logistic regression model and analysis of odds ratios (OR) were employed to evaluate the risk factors associated with E. coli infection, and statistical significance was attributed to p values of ≤ 0.05.Out of the 220 urine samples examined, 42 (19%) exhibited a positive culture indicating E. coli infection in pregnant women. Our analysis revealed that income, gestational age, and a history of UTIs were identified as risk factors associated with E. coli infection. Most E. coli isolates demonstrated sensitivity to Amikacin (100%), Nitrofurantoin (85.7%), Amoxicillin/clavulanic acid, and Meropenem (83.3%).The prevalence of E. coli was remarkable. It could be recommended that pregnant women in antenatal care should have routine culture and antimicrobial susceptibility tests to prevent transmission of resistant pathogens and complications in both pregnant mothers and the unborn baby.